INTEGRASI DAN EVALUASI DIMENSI BERIMAN DAN BERTAKWA DALAM PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5): STUDI EVALUATIF DI SDN CIREUNDEU 02 - Tesa Rama Primadona; Mahmudin Sudin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to evaluate the integration and implementation of the faith and piety dimension within the Pancasila Student Profile Strengthening Project (P5) at SDN Cireundeu 02. Using a descriptive qualitative approach with data collection methods including interviews, observations, and documentation, the study involved Islamic Religious Education (PAI) teachers, P5 coordinators, and students as subjects. The results indicate that the use of measurable assessment rubrics successfully enhanced students' spiritual awareness and moral behavior, with increased participation in religious activities and positive conduct. However, challenges were identified in the consistency of teacher assessments and limited understanding of evaluation indicators. To address these issues, teacher training and increased parental involvement are recommended as solutions. This research contributes to the development of a more objective and holistic character assessment system within the framework of the Merdeka Curriculum.